2016
DOI: 10.1155/2016/6731093
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Associated Changes in the Vascular Renin‐Angiotensin System in Mice

Abstract: Background. This study evaluated whether the change in the renin-angiotensin system (RAS) is associated with arterial aging in mice. Methods. Histologic changes and expressions of transforming growth factor-β (TGF-β), collagen IV, fibronectin, angiotensin II (Ang II), angiotensin-converting enzyme (ACE), angiotensin-converting enzyme 2 (ACE2), angiotensin II type 1 receptor (AT1R), angiotensin II type 2 receptor (AT2R), prorenin receptor (PRR), Mas receptor (MasR), endothelial nitric oxide synthase (eNOS), NAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
110
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(129 citation statements)
references
References 52 publications
16
110
0
Order By: Relevance
“…9 Decreasing ACE2 is notable in animal models of ageing. 10 Sodhi et al demonstrated that neutrophil inflammation following bacterial pneumonia was altered by pulmonary ACE2 activity. Alterations in ACE2 are critical for neutrophil influx and lung inflammation.…”
Section: Angiotensin-converting Enzyme 2 (Ace2) Receptormentioning
confidence: 99%
“…9 Decreasing ACE2 is notable in animal models of ageing. 10 Sodhi et al demonstrated that neutrophil inflammation following bacterial pneumonia was altered by pulmonary ACE2 activity. Alterations in ACE2 are critical for neutrophil influx and lung inflammation.…”
Section: Angiotensin-converting Enzyme 2 (Ace2) Receptormentioning
confidence: 99%
“…With renal aging, there is an elevated activation of the vascular renin‐angiotensin‐aldosterone‐system (RAAS), leading to increased levels of angiotensin II in the arterial wall. The downstream effect of RAAS activation is the upregulation of tumor growth factor‐beta (TGF‐β), which subsequently increases collagen production and deposition into ECM, resulting in vascular thickening . Furthermore, oxidative stress also upregulates matrix metalloproteinase development and further increases vascular fibrosis leading to LV remodeling and subsequent deleterious CV aging .…”
Section: Molecular and Cellular Changesmentioning
confidence: 99%
“…The downstream effect of RAAS activation is the upregulation of tumor growth factorbeta (TGF-β), which subsequently increases collagen production and deposition into ECM, resulting in vascular thickening. 39 Furthermore, oxidative stress also upregulates matrix metalloproteinase development and further increases vascular fibrosis leading to LV remodeling and subsequent deleterious CV aging. 40,41 Table 1 summarizes the common age-associated changes that occur in the CV system and their potential relationship to developing CV disease.…”
Section: Extracellular Matrixmentioning
confidence: 99%
“…This evidence is the result of findings from the Lakatta s' group, using rat models, [62,63], and Šabovic's group [64], who propose administering combination of low-dose fluvastatin and valsartan, as anti-aging drugs. On the other hand, the expression and activity of Ang II, the angiotensin converting enzyme (ACE), the Ang II receptor AT1 receptor within the aorta wall, in particular, in the thickened intima in several species, including humans, are risen as the age progress [62][63][64][65][66][67][68][69][70][71]. Interestingly, also the chymase, another angiotensin-convertase, was found in the wall of aged aorta [69].…”
Section: Structural and Functional Features Of The Aorta In Physiologmentioning
confidence: 99%